Halal development and food exports: evidence from Malaysia and the Middle Eastern Asian Countries - Tajul Arffin Masron; Nik Hadiyan Nik Azman; Siti Hasnan Hassan (Penerbit Universiti Kebangsaan Malaysia, 2014)
Exports remain an important growth enginefor Malaysia, and the ability to maintain or improve the level of exports is a crucialfactor to sustain and boost Mdlaysiab ebonomic growth. Combinedwith extensive development in halal-related areas, especially in food production, Malaysia should be able to further intensify its exports, particularly to Islamic countries, such as the Middle Eastern Asian Countries (ualcs). Whether or not halal development is confributing to the expansion ofexports is yet to be researched. Therefore, this study attempts to investigate the potential role played by halal development in Malaysia on its exports. Considering this is among the earlier studies examining the implication of the halal development on exports, this study limits the scope to cover the exports of Malaysiato the MEACs only. Applying panel data approach, this study found limited evidence that halal industry has played role in promoting Malaysianfood exports to MEACr.